Cutaneous Metastasis of Ovarian Tumor after Hysterectomy and Bilateral Salpingo-oophorectomy: A Case Report - Hamid Naeem; Qazi Muhammad Farooq Wahab; Junaid Imran; Mazhar Khalil (Gandhara University, 2024)
OBJECTIVES Cutaneous metastases are a very rare presentation of ovarian tumors (OV). They occur in about 3.5 percent of cases. The prognosis of cutaneous metastases is not good despite recent treatment modalities. Researchers are looking for much more personalized treatments.  The patient had a history of ovarian tumor, for which she had a hysterectomy and bilateral salpingo-oophorectomy. She presented with multiple cutaneous eruptions. The histopathology shows high-grade serous carcinoma of the ovaries. Immunochemistry is positive for cytokeratin 7, WT1, and CAX. She had developed left leg swelling, generalized edema, and complaints of dysuria and difficulty defecating. Many targeted therapies have been developed, such as inhibiting growth factor receptors and immunological treatments that induce cell death, opening the door to precision medicine.